Novejši pristopi v analizi podatkov o smrtnosti - Simona Korenjak-Černe; Aleša Lotrič Dolinar (Economic and Business Review, 2019)
In the application of statistical methods and models, as well as other data analysis methods, we encounter a number of limitations that make it necessary to find new approaches. The purpose of this article is to highlight the rationale for seeking new approaches to the analysis of mortality data in European countries observed by sex, age, and cause of death, to briefly present some results of recent work, and to point to research being conducted in collaboration with other researchers on this information.